Delivering the Goods Building Local Government Capacity to Achieve the Millennium Development Goals - Roger Shotton , Mike Winter (Library of Congress, 2005)
This Practitionerâ€™s Guide has been long in the making â€“ longer even than the 22 month gestation period enjoyed by elephants. But I believe that it has been worth it. It is an important publication for several reasons. Firstly, and more parochially, UNCDF is an organization which has always prided itself on its internal learning and policy-development processes. We therefore attach a great deal of importance to this kind of attempt to capture and â€œcodifyâ€ the various sorts of lessons which are emerging from our growing portfolio of Local Development Programmes â€“ which are now active in some 25 Least Developed Countries. In doing so it also provides a common language or framework (a set of organizing â€œboxesâ€) which can be used to continually update and further enrich the lesson-learning process in the future. Secondly, however, I believe that this Guide should be of wider interest and application â€“ both within UNDP and in the wider circle of development practitioners. The recent Millennium Report to the UN Secretary General highlighted the urgent need for â€œscaleable modelsâ€ to ensure that basic infrastructure and service delivery is expanded sufficiently to meet the 2015 targets. The guidelines and lessons highlighted in this Guide provide the elements for developing such models: â€¢ They focus on delivering those types of basic primary infrastructure and associated services that the poor need; â€¢ They are geared to the specific challenges of rural and difficult areas â€“ where the MDG deficits are greater and the problems in improving delivery far more daunting than in big cities, and where â€œgood practicesâ€ are thin on the ground; â€¢ They work on reforming delivery systems within the existing national policy and institutional frameworks of local government organizations and procedures, so that they can be the more readily adopted and upscaled (as they already have been in several LDCs); â€¢ They are adaptable to differing contexts; â€¢ They are based on live operational experience, and have a string of attested positive results to their credit. As the Introduction makes quite clear this is not, however, a cookbook. It simply aims to provide a guiding framework, some insights, and continual reminders of the trade-offs and challenges to be faced for those who are charged with promoting better local infrastructure and service delivery and local governance in difficult areas. It is a first version â€“ based on user and reader feedback. We hope to regularly revise, correct and enrich this Guide in later versions.